A Dynamic Analysis of the Adoption of a New Technology: The Case of Optical Scanners - Levin, Sharon G.; Levin, Stanford L.; Meisel, John B. (The Review of Economics and Statistics, 1987)
Two p roportional hazard models are used to investigate the differingeffects of marke t structure variables on the conditional probabilityof a firm initially adoptin g the new technology of optical scanners as the innovation spreads through the f ood store industry. During the early stage, leading firms with large average sto re size which are not members of chains and which operate in less concentrated m arkets with higher incomes and wage rates, tend to adopt scanners sooner. Later on, differences in seller concentration, market share, and size become less impo rtant as other firms follow prior adoptions. Copyright 1987 by MIT Press.